Extending the slip model of polycrystalline plasticity for the general plane deformation - Dan, Bui Huu; Kratochvil, J.; Satra, M. (Vietnam Journal of Mechanics, 1991)
The computation procedure of the slip model polycrystalline plasticity was extended for the general broken three-dimensions strain trajectories (approximately for arbitrary three-dimensions trajectories). The system of equations determining the model plane and the coordinate system on it was given and solved. The procedure was applied for some special type of tralections. The anisotropy, delay effect and saturated effect of the plastic deformation has been shown and estimated.